Start-up and shut-down strategies of DR-based hybrid DC converter for offshore wind power transmission system - Fang, Zixi; Yang, Renxin; Han, Kun; Cai, Xu; Hong, Bo; Liu, Lulu (Frontiers in Energy Research, 2023)
The diode rectifier (DR) based hybrid dc converter can significantly increase the economy of the offshore wind power transmission system comparing with the traditional modular multilevel converter (MMC). However, the start-up and shut-down methods of this hybrid dc converter are not studied. In this paper, the start-up and shut-down strategies of the hybrid dc converter are proposed. The start-up process can be divided into two stages: uncontrollable precharging stage and controllable precharging stage. In the uncontrollable precharging stage, the calculation method of the precharging current is given and the design method of the current limiting resistor is presented. In the controllable precharging stage, a circulating current control strategy is proposed to balance the inner energy of the converter and charge the submodule capacitors to the rated value. Besides, the corresponding shut-down strategy is also introduced which can discharge the submodule capacitors quickly and safely. Simulation results based on MATLAB/Simulink and hardware-in-the-loop experiment results based on the RT-LAB are provided to support the proposed strategies.